Пропозиція і попит – основні чинники впливу на вартість нерухомості - Нестеренко, І. С. (Ways to Improve Construction Efficiency, 2014)
The basic factors which form suggestion and demand of objects of the real estate their interconnection are resulted, that results in the most credible price at the market of the real estate.